Why this Kolaveri about Teaching Vowel Sounds at HKG Level - Arora, Sanjay; Arora, Anshika (THE PRIMARY TEACHER, 2017)
There is an aggressive rage or haste (kolaveri) in India to teach spoken English (especially, in English medium schools) because of the increasing demand of urban elite and middle class parents to make their wards learn fluent English. Parents coming from economically weaker sections of society, too, have become aware of the importance of English due to media exposure, including social media. The article is based on teaching vowel sounds (through one of the English textbooks) to children at the higher kindergarten (HKG) level at a public school in Jaipur. The first part of the paper discusses how the teaching of vowel sounds is undertaken at this level through the textbook, Step Up with English Primer. This is followed by a discussion on how teaching from such books can distort the very foundation of students and induce inappropriate learning style in them. The paper emphasises teaching of sounds as these are considered to be the base of spoken English.